TAPAS: Building a TEI Publishing and Repository Service - Julia Flanders; Scott Hamlin (Journal of the Text Encoding Initiative)
This project report details the goals and development of the TEI Archiving, Publishing, and Access Service (TAPAS). The project's mission centers on providing repository and publication services to individuals and small projects working with TEI data: a constituency that typically lacks access to institutional resources such as server space, XML expertise, and programming time. In developing this service, TAPAS addresses several important challenges: the creation of a publication ecology that operates gracefully at the level of the individual project and the TAPAS corpus; the problem of the vulnerability of TEI data in cases where projects cease their activity; and the variability and complexity of TEI data. When completed, the TAPAS service will enable its contributors to upload, manage, and publish their TEI data, and it will offer a publication interface through which both individual project collections and the TAPAS collection as a whole can be read, searched, and explored. It will also provide a range of related services such as technical consulting, data curation and conversion work, TEI workshops, tutorials, and community forums. This article discusses the philosophy and rationale behind the project's current development efforts, and examines some of the challenges the project faces.